What Support? Foucault, Power, and the Construction of Rape - Aliraza Javaid (Qualitative Sociology Review, 2019)
This paper is concerned with the social and cultural constructions of male rape in voluntary agencies, England. Using sociological, cultural, and post-structural theoretical frameworks, mainly the works of Foucault, I demonstrate the ways in which male rape is constructed and reconstructed in such agencies. Social and power relations, social structures, and time and place shape their discourses, cultures, and constructions pertaining to male rape. This means that constructions of male rape are neither fixed, determined, nor unchanging at any time and place, but rather negotiated and fluid. I theorize the data—which was collected through semi-structured interviews and qualitative questionnaires—including male rape counselors, therapists, and voluntary agency caseworkers. The theoretical and conceptual underpinnings that frame and elucidate the data contribute to sociological understandings of male rape.